2017
DOI: 10.7554/elife.20873
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the MAD2L1 spindle assembly checkpoint gene is tolerated in mouse models of acute T-cell lymphoma and hepatocellular carcinoma

Abstract: Chromosome instability (CIN) is deleterious to normal cells because of the burden of aneuploidy. However, most human solid tumors have an abnormal karyotype implying that gain and loss of chromosomes by cancer cells confers a selective advantage. CIN can be induced in the mouse by inactivating the spindle assembly checkpoint. This is lethal in the germline but we show here that adult T cells and hepatocytes can survive conditional inactivation of the Mad2l1 SAC gene and resulting CIN. This causes rapid onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 58 publications
9
64
0
Order By: Relevance
“…However, MEFs become much more tolerant of CIN when p53 was also deleted, [23] although long term cultures of SAC-deficient MEFs are difficult to maintain. [72] Similar to what is observed in vitro, high-grade CIN is not tolerated when provoked early in development: for instance full SAC abrogation through Mad2 inactivation in the mouse, with or without p53 deletion, yields early embryonic death. [23,73] However, high-grade CIN is not always lethal in vivo.…”
Section: Cin Can Have Highly Differential Effects On Cellsmentioning
confidence: 71%
See 3 more Smart Citations
“…However, MEFs become much more tolerant of CIN when p53 was also deleted, [23] although long term cultures of SAC-deficient MEFs are difficult to maintain. [72] Similar to what is observed in vitro, high-grade CIN is not tolerated when provoked early in development: for instance full SAC abrogation through Mad2 inactivation in the mouse, with or without p53 deletion, yields early embryonic death. [23,73] However, high-grade CIN is not always lethal in vivo.…”
Section: Cin Can Have Highly Differential Effects On Cellsmentioning
confidence: 71%
“…[75,93,94] Furthermore, yet other CIN models are suggesting that CIN only enhances tumorigenesis in a tumorprone background. [16,32,72,95,96] These inconsistent findings may be explained by different rates and types of CIN in the various models. Indeed, it has been suggested that high rates of CIN inhibit tumor progression, while lower CIN rates allow for tumor evolution [5,93,94] (also see Figure 2b and c).…”
Section: Cin Can Have Highly Differential Effects On Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mouse models of CIN have occasionally shown sporadic, spontaneous tumors with very long latency (>12-18 months), and predominantly in spleen and lung [21][22][23][24][25][26][27][28][29] , suggesting CIN is not a potent cancer driver. In mice predisposed to cancer, CIN is either neutral [30][31][32] , promotes tumor formation 23,26,27,30,[33][34][35][36][37][38][39] , or, in some conditions, suppresses it 29,30,32,37 .…”
Section: Introductionmentioning
confidence: 99%